Support Factors of Self Foot Care for Diabetes Mellitus Patients - Rohmatul Faizah; Gabriel Wanda Sinawang; Andrik Hermanto; Mohamad Roni Alfatih (Universitas Airlangga, 2019)
Introduction: Diabetes mellitus is a chronic disease of the endocrine system that has numerous complications such as diabetic foot ulcers. Amputation is the last frontier for the treatment of diabetic foot ulcers but they can be prevented through proper self-foot-care behavior. The aim of this study was to explain the support factors of self foot care for diabetes mellitus patients.Methods: The methods used were self-foot-care identification in the literature, with the relevant literature identification based on the topics and titles obtained from Scopus, ScienceDirect and ProQuest. This was as well as analysis of the results from examining the various behaviors that support self-foot-care behavior in the literature. The references included was the research conducted from 2013 - 2019 as follows: 2 descriptive correlation studies, 3 descriptive studies, 2 prospective studies, 1 prospective cohort study, 1 pre-experimental study, 3 quasi-experimental studies, 1 case study and 3 cross-sectional studies.Results: All of the journals included discussed foot care behavior. Education programs regarding foot care are a major factor that supports foot care behavior.Conclusion: All of the journals that were obtained stated that there was a positive influence on the diabetic foot condition where routine foot care behavior was implemented. Self-foot-care behavior also requires other supporting factors to obtain the maximum results.